Medical Advice for Sick-reported Students (MASS) in intermediate vocational education schools: design of a controlled before-and-after study - Madelon K Van der Vlis; Marjolein Lugtenberg; Yvonne T.M. Vanneste; Wenda Berends; Wico Mulder; Rienke Bannink; Amy Van Grieken; Hein Raat; Marlou L.A. de Kroon (BMC, 2017)
Abstract Background School absenteeism, including medical absenteeism, is associated with early school dropout and may result in physical, mental, social and work-related problems in later life. Especially at intermediate vocational education schools, high rates of medical absenteeism are found. In 2012 the Dutch intervention 'Medical Advice for Sick-reported Students' (MASS), previously developed for pre-vocational secondary education, was adjusted for intermediate vocational education schools. The aim of the study outlined in this paper is to evaluate the effectiveness of the MASS intervention at intermediate vocational education schools in terms of reducing students' medical absenteeism and early dropping out of school. Additionally, the extent to which biopsychosocial and other factors moderate the effectiveness of the intervention will be assessed. Methods A controlled before-and-after study will be conducted within Intermediate Vocational Education schools. Schools are allocated to be an intervention or control school based on whether the schools have implemented the MASS intervention (intervention schools) or not (control schools). Intervention schools apply the MASS intervention consisting of active support for students with medical absenteeism provided by the school including a consultation with the Youth Health Care (YHC) professional if needed. Control schools provide care as usual. Data will be collected by questionnaires among students in both groups meeting the criteria for extensive medical absenteeism (i.e. 'reported sick four times in 12 school weeks or for more than six consecutive school days' at baseline and at 6 months follow-up). Additionally, in the intervention group a questionnaire is completed after each consultation with a YHC professional, by both the student and the YHC professional. Primary outcome measures are duration and cumulative incidence of absenteeism and academic performances. Secondary outcome measures are biopsychosocial outcomes of the students. Discussion It is hypothesized that implementing the MASS intervention including a referral to a YHC professional on indication, will result in a lower level of medical absenteeism and a lower level of school drop outs among intermediate vocational education students compared to students receiving usual care. The study will provide insight in the effectiveness of the intervention as well as in factors moderating the intervention's effectiveness. Trial registration Nederlands Trial Register NTR5556. Date of clinical trial registration: 29-Oct-2015.